Personality and academic achievement in nniversity students - Niño de Guzmán, Isabel (2003)
The correlations among personality, academic performance and other variables in 170 university students were studied, using two instruments validated into the population: the NEOPJ-R, and the EPPS. Other variables as age, study level, self perception of academic achievement and self perception of motivation, and sources of support were included. Jt was confirmed the reliability and validity of both tests and the correlations between them. The results showed associations among academic performance and conscientiousness, endurance,change, and aggression. The academic performance was better explained by achievements triving, deliberation, change, self perception of academic achievement and age.